Boron exchange between the sea and the atmosphere. - Bruevich, Semyon V; Korzh, Vyacheslav D (PANGAEA, 1971)
Boron and chlorine were determined in rain water and in atmospheric moisture condensed in a "Saratov" refrigerator. Ocean is the main source of boron on the earth surface. Boron evaporates from the ocean and enriches atmospheric precipitation: B/Cl ratio of ocean water (0.00024) increases by factor of 10-15. Assuming that the average Cl content in global river runoff is 7.8 mg/l and boron content 0.013 mgl, B/Cl ratio in this runoff is 0.0017. The average B/Cl ratio in rain water of the Golubaya (Blue) Bay (Gelendzhik, Black Sea region) is 0.0026 and in condensates of atmospheric moisture during onshore and offshore winds in the same region it averages from 0.0029 to 0.0033. The maximum boron content in the condensates of this region during onshore winds was 0.032 mg/l and the minimum during offshore winds, 0.004 mg/l. /Cl ratio in sea water over the Atlantic Ocean and in the Gelendzhik area of the Black Sea varied within narrow range, mostly from 0.0025 to 0.0035. Similar B/Cl ratio (0.0024) was found for atmospheric precipitation on the slope of the Terskei Ala-Tau near the Issyk-Kul Lake in 1969. Thus, although chemistries of boron and chlorine (in chlorides) are very different, the B/Cl ratio in the atmosphere is fairly constant. This can be taken as a confirmation of an assumption that salt composition of sea water passes into the atmosphere in molecularly dispersed state. Supposing that the ocean-atmosphere system is in equilibrium as regards to the boron budget, it can be assumed that the same amount of boron passes from the ocean into bottom sediments and from lithosphere rocks and soils into the hydrosphere.
(Table 3) Boron and chlorine in atmospheric moisture and rain water collected on the shore of the Golubaya Bay in 1970
Keywords: Archive of Ocean Data; ARCOD; Boron; Boron/Chlorine ratio; Chloride; Chlorine; Comment; Date; Duration; GB-SBIOAS; Humidity, relative, minimum; Mikhail Lomonosov; ML19; RAIN; Rain water collector; Red Sea; Sample code/label; Sample volume; Titration; Wind direction description; Wind speed, maximum